Deconstructing Islamic Religious Education (IRE) Materials to Foster Multicultural Awareness Among Millennial Students - Farouq, Yazdan; Khalil, Mazin; Yahya, Thaufiq Ilham Dwi (Multicultural Islamic Education Review, 2025)
Indonesia’s cultural and religious diversity presents both an opportunity and a challenge for education. However, Islamic Religious Education (IRE) in schools remains largely normative and ritualistic, offering little engagement with multicultural values. This study aims to deconstruct IRE materials to promote multicultural awareness among millennial students. Using a qualitative descriptive method with a case study approach, data were collected through interviews, observations, and document analysis involving teachers, students, and school leaders in socially diverse senior high schools. The findings reveal that current IRE textbooks predominantly emphasize jurisprudence and theology while marginalizing themes of tolerance and interfaith dialogue, resulting in varied student attitudes toward diversity—from inclusive to exclusivist. By applying deconstructive strategies such as contextual reinterpretation of Qur’anic verses, incorporation of cross-cultural case studies, and the use of digital media and experiential learning, teachers can reshape IRE into a more inclusive, humanistic, and context-sensitive subject. This study implies the need for systemic curriculum reform and teacher professional development to align Islamic education with the values of pluralism and democratic coexistence, thereby strengthening social cohesion among Indonesia’s youth.